Flexural behaviour of plain concrete prism strengthened by textile fine grained mortar - Jamellodin, Zalipah; Mohd Saman, Hamidah; Adnan, Suraya Hani; A. Khalid, Nur Hafizah; Abdul Hamid, Noor Azlina; A. Majid, Masni; Salleh, Norhafizah (American Scientific Publishers, 2018)
This paper presents a flexural strength study of concrete incorporated with textile fine grained mortar (TFGM) as a strengthening laminate. TFGM is a combination of fine grained mortar (FGM) with alkali resistant glass fabric (AR glass). Fine grained sand with 600 m maximum size was used in FGM and fly ash (FA) or rice husk ash (RHA) has been used as a partial substitute for ordinary Portland cement (OPC). The potential of TFGM as strengthening laminate was tested under monolithic load with three point flexure loading. The TFGM were laid in layers of two, four, six, and eight. Results shown a promising flexure enhancement of up to three times of unstrengthened concrete when eight layers of both RHA and FA were laid. Load bearing capacity and ductility of the samples increased about 200% and 61%, respectively, compared to control samples as well. The outcome shows a highly potential use of agro-waste as cement replacement to produce load bearing structural components